ERGONOMICS IN WORK ENVIRONMENT AND ITS CONTROL - PANKAJKUMAR VASANT AMALE; DR S V BANSOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The principal objective of Ergonomics is to fit the task to the user and not the user to the task. Incorporating Ergonomics principles in the work environment guarantees productivity, quality, reliability and job satisfaction while maintaining sound occupational health and safety. The purpose of this paper is to identify various critical components of ergonomics work environment and their control with a proactive approach. The critical components are Anthropometry, work related musculoskeletal disorders, manual material handling, workstation design for static works.